IMPACT OF THE COVID-19 PANDEMIC FOR MSMEs IN EFFORTS TO INCREASE INCOME - Stepanus Sandy; Rulan L. Manduapessy; Johanis Nifanngeljau; Tharsisius Pabendon (UPT Publikasi Ilmiah UNISBA, 2023)
The purpose of this research is to directly find out that there is a COVID-19 outbreak that has a much bigger impact on Micro, Small and Medium Enterprises in an effort to increase income. This research was conducted in Pasar Rentra Village, Mimika Baru District, Mimika Regency. This research uses a qualitative descriptive method as well as data or information collection techniques in the form of ongoing interviews with 10 informants who have the profession of Micro, Small and Medium Enterprises as representatives of MSMEs in the Mimika Baru District Rentra Market. The results found in this research are regarding the spread of the existing COVID-19, so that it will directly have a very significant impact on Micro, Small and Medium Enterprises. The impact is grouped into several parts, including: (a) income has decreased drastically; (b) lack of consumers; and (c) raw material prices have increased. Therefore, it is necessary for MSMEs to be able to sell online, open a side business, provide good service, and pay attention to the quality of the goods to be sold. Keywords: Impact of COVID-19, MSMEs, Business Income.